Democracy, Transformation and the Relational Economy: Prospects for a Successful Society - Messal, Michael; Dommes, Marc; Schwunk, Felix (HAPSc Policy Briefs Series, 2020)
Not least because of existential crises such as climate change, poverty or social inequality, the transformation currently taking place is changing the way people live together in a sustainable manner. However, such challenges can only be overcome by humanity as a whole. Therefore, it is necessary to develop new collective problem solving modes that take into account the relationship of the individual to his environment. As a starting point for this, we propose the introduction of a systemic-relational economy which, starting from companies, establishes a holistic world view oriented towards the growth of good relationships. This is the preferable way to meet the changing demands of modern life and to achieve ecologically, economically and socially sustainable success.